A Natural Series for the Natural Logarithm - Dasbach, Oliver T. (The Electronic Journal of Combinatorics, 2008)
Rodriguez Villegas expressed the Mahler measure of a polynomial in terms of an infinite series. Lück’s combinatorial L^2-torsion leads to similar series expressions for the Gromov norm of a knot complement. In this note we show that those formulae yield interesting power series expansions for the logarithm function. This generalizes an infinite series of Lehmer for the natural logarithm of 4.